The Fiscal Role of Price Stabilization Funds : The Case of Cote d'Ivoire. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper aims to illustrate the important fiscal aspects of an agricultural price stabilization fund by examining the operations and experience of the CSSPPA in Cote d'Ivoire. After considering some of the issues that determine whether a price stabilization fund should be in the private or public sector and investigating the fund's resource mobilization role through explicit and implicit export taxation, the paper discusses issues related to the adequate insulation of producer prices from changing world market prices, and provides a macroeconomic perspective of the fund's role in the transmission of export stimuli to the domestic economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet